The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1097/sle.0000000000001035
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of eTEP and IPOM in Ventral and Incisional Hernia Repair: A Systematic Review and Meta-analysis

Abstract: Background: Open sublay technique and laparoscopic intraperitoneal onlay mesh (IPOM) technique are the most common used procedures in ventral and incisional hernia repair, however, each technique has its own disadvantages. The enhanced view total extraperitoneal technique (eTEP) aims to put the mesh in the retromuscular space by minimal invasive technique. This study is to investigate the efficacy and safety of eTEP and IPOM approach in ventral and incisional hernia repair.Methods: The major databases (PubMed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…A systematic review and meta‐analysis comparing eTEP and IPOM (a total of 433 patients) showed longer operative duration, lower postoperative pain scores, and shorter hospital stay in the eTEP group. However, the rates of intraoperative complications and postoperative ileus, seroma, and hematoma were similar 29 …”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…A systematic review and meta‐analysis comparing eTEP and IPOM (a total of 433 patients) showed longer operative duration, lower postoperative pain scores, and shorter hospital stay in the eTEP group. However, the rates of intraoperative complications and postoperative ileus, seroma, and hematoma were similar 29 …”
Section: Discussionmentioning
confidence: 80%
“…However, the rates of intraoperative complications and postoperative ileus, seroma, and hematoma were similar. 29 In a systematic review of minimally invasive (laparoscopic/robotic) component separation techniques (CST), posterior CST-TAR showed a lower length of hospital stay (2.4 ± 1.4 vs. 7.2 ± 2.1 days) and recurrence rates (0.4% vs. 6.6%), with no significant difference in surgical complication rates (17.8% vs. 15.8%) when compared with minimally invasive anterior CST. 30 To the best of our knowledge, this is the first report on outcomes after ventral hernia repair in the Philippines, which focused on a MIS approach.…”
Section: Discussionmentioning
confidence: 99%
“…Addo et al 9 reported 461 patients undergoing laparoscopic or robotic retromuscular repairs and found no differences in recurrences or complications when comparing patients with BMI >35 kg/m 2 or <35 kg/m 2 . Although we were unable to perform a subgroup analysis of different surgical techniques, a meta-analysis comparing enhanced total extraperitoneal and IPOM showed no difference in postoperative complications, but this is an area of ongoing research, and a randomized clinical trial is currently ongoing to compare both techniques (NCT04150796) 27 …”
Section: Discussionmentioning
confidence: 96%
“…Although we were unable to perform a subgroup analysis of different surgical techniques, a meta-analysis comparing enhanced total extraperitoneal and IPOM showed no difference in postoperative complications, but this is an area of ongoing research, and a randomized clinical trial is currently ongoing to compare both techniques (NCT04150796). 27…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review by Li et al (2022) suggested eTEP was associated with reduced LOS, however no significant difference was found in intraoperative and postoperative complications. 53 Recurrence in hernia surgery is an important outcome as it affects quality of life and may require re-operation. The assessment of recurrence in RVHR is limited, as most available studies have follow-up periods of under 1 year, and recurrence often develops following this period.…”
Section: Discussionmentioning
confidence: 99%